Analysis of the Mathematical Ability of Junior High School Students in terms of the Extrovert-Introvert Personality Type - Tsaniya, Ninda Putri; Darta, Darta; Fisher, Dahlia (IndoMath: Indonesia Mathematics Education, 2022)
Mathematical abilities that are the basis of mathematical problem solving skills, mathematical communication skills, mathematical reasoning abilities, mathematical connection abilities, mathematical representation abilities. This study aims to describe the mathematical ability of junior high school students in terms of the extrovert-introvert personality type. The results of the study will be used as the main library material in the implementation of the next research. This study specifically discusses Carl Gustav Jung's personality type which distinguishes two personality types, namely introverted and extroverted personalities. The type of research used in this study is a literature study research method. The data sources in this study are literature or come from various literatures, including books, journals, newspapers, personal documents and so on. Sources of data used in this study are primary data sources and secondary data sources. Data collection techniques used are Editing, Organizing, and Finding. For data analysis using deductive, inductive, and interpretative. The results of this literature study show: junior high school students with introverted personality types have good mathematical abilities compared to students with extroverted personality types.